The Influence of Quality of Work Life on Individual Commitment in Organizations Mediated by Self-Efficacy: A Study on Teachers at Islamic High School in Malang City - Danni Marindra; Adya Hermawati; Alfiana (Optima Science, 2026)
This research is motivated by the low level of teacher commitment and a lack of ownership towards their workplace. Based on an initial survey conducted by the researcher on 37 teachers at SMA